Factors Influencing Tax Compliance Among Micro and Small-Sized Enterprises in Masinloc, Zambales (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This study investigated factors influencing tax compliance among micro and small-sized enterprises (MSEs) in Masinloc, Zambales, Philippines (CY 2022-2023). We used a quantitative descriptive survey design with 119 randomly selected MSE owners and questionnaires. The study profiled respondents based on age, gender, business type and size, income, and employee count. Perceived factors influencing tax compliance were assessed across seven dimensions: tax knowledge, morale, attitudes/ethics, municipal tax system efficiency, fairness, compliance costs, and perceived behavioral control. The results showed a predominantly female, middle-aged population of MSE owners who were primarily engaged in merchandising. We observed a high level of tax compliance (86.55%). While respondents demonstrated strong knowledge of tax laws and a positive attitude towards compliance, significant differences in perceptions emerged concerning municipal tax fairness, notably influenced by age. Analysis revealed a positive moderate relationship between the seven factors and overall tax compliance. The study concludes with recommendations for enhanced tax education programs, streamlined tax processes, and targeted support for MSEs, suggesting further research to validate these findings in a broader context.